Taxes and Organizational Change: A Management Theory Review - Mira Lestari (Manunggal Halim Jaya, 2023)
This study investigates the intricate relationship between taxation policies and organizational dynamics, focusing on the influence of taxes on strategic decision-making, resource allocation, and corporate governance. Employing a qualitative research methodology, the study conducts a systematic review of relevant literature from management, accounting, economics, and taxation domains. Thematic and content analyses are employed to synthesize key insights and patterns from the literature, revealing significant findings regarding the impact of taxation on organizational behavior. The results highlight the multifaceted influence of taxation policies on strategic decision-making processes within organizations, particularly among multinational corporations (MNCs). Tax considerations drive investment decisions, organizational structures, and international expansion strategies, shaping strategic outcomes and financial performance. Additionally, the study underscores the importance of effective tax planning and governance mechanisms in mitigating tax risks, enhancing shareholder value, and upholding ethical standards. Managerial implications suggest the need for organizations to adopt a proactive approach to tax management, integrating tax considerations into strategic planning frameworks, and fostering a culture of compliance and transparency. Overall, the study contributes to theoretical understanding and managerial practice in navigating the complexities of taxation dynamics in contemporary business environments.